Sejarah Penulisan Al-Qur’an Mushaf Sundawi di Bandung Tahun 1995-1997 - Billy Muhammad Rodibillah; Ajid Thohir; Aam Abdillah (UIN Sunan Gunung Djati Bandung, 2018)
ago, along with the development of Islamic culture which acculturated with culture in the archipelago. Accordingly, the writing tradition of the Quran formed the typical Al-Qur'an manuscripts in terms of calligraphy also in terms of illumination (appearance). Likewise the Al-Qur'an of the Sundawi Mushaf which was written in the last decade of the 20th century, precisely in 1995. The writing was carried out in Bandung, at the initiative of the then Governor of West Java, R. Nuriana. Al-Qur'an, Sundawi Mushaf has its own characteristics, both in terms of writing (calligraphy) and in terms of appearance (illumination), so that these characteristics become distinguishing with other manuscripts. The writing of the Al-Qur'an in 'Sundawi manuscripts was carried out on August 14, 1995 to January 25, 1997 on the initiative of the Governor of West Java at the time, R. Nuriana, based on Governor Decree No. 451.05 / SK.1196-Binsos / 95. Conceptually, Al-Qur'an Sundawi Mushaf is a harmonious blend of revelation texts of the Qur'an with the cultural treasures of West Java that are socio-culturally included in the Pasundan culture. From the conceptual framework, the special characteristic of the calligraphy system was found and the typical illumination design was lifted from the variety of ornamental and flora found in Pasundan land, so that this manuscript has a distinctive appearance with the